Formability improvement in die less forming process of Ti Gr. 2 perforated sheet: experimental method and finite element analysis - Gurpude R.R.; Mulay A.; Sharma P. (My University, 2025)
The SPIF technique stands out as a versatile method aimed at forming sheet metal components, especially in circumstances where production volumes are limited. A crucial aspect in SPIF revolves around maintaining meticulous control over process variables to ensure that fabricated components stick to required dimensional specific production. This study focuses on influence of variable process factors on formability of perforated Ti Gr.2. The investigation primarily investigates into geometrical factors such as tool and hole diameters, recognizing their key role in defining formability of perforated sheet. The numerical simulations is conducted through ABAQUS® software serve as backbone of this investigation. As temperature levels rise, the materials ductility proportionally increases, rendering the sheet more ductile and easier for forming. The outcomes derived from the experiments highlight the deep impact of hole diameter on material formability. Furthermore, study investigates into assessment of Von-Mises stresses, plastic equivalent strain (PEEQ), and thickness distribution across varied input process parameters. Remarkably, the results expose a direct correlation between hole size and fracture depth, exposing a critical aspect of material behaviour under SPIF conditions. Moreover, the analysis extends to examining variations in microstructure and hardness between the as received material and optimal formed samples. © The Author(s), under exclusive licence to Springer-Verlag France SAS, part of Springer Nature 2024.